Effect of Al-Mergheb Portland Cement Factory On Vegetation Cover - Aly Okasha (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Al-Mergheb Portland Cement Production plant is located near Al-Khoms city in the eastern part of the Jefarah plain which is known for its good biodiversity. The impact of the Al-Mergheb Cement Factory on vegetation cover in the surrounding area is classified into two major trends depending on the prevailing wind direction in the region. The biodiversity of vegetation is estimated using the squares method at selected sites taking wind directions into account. The study concludes that the emitted cement emissions from the plant has a substantial negative impact on the vegetation in the study area. Vegetation diversity and density is consistently reduced towards the emission site. The study shows that vegetation east of the plant is more diverse that toward the south.